Lead perovskites as CEνNS detectors - Jesús-Valls, César; Sánchez, Federico (Frontiers in Physics, 2023)
The recent discovery of Coherent Elastic neutrino-Nucleus Scattering (CEνNS) has created new opportunities to detect and study neutrinos. The interaction cross-section in CEνNS scales quadratically with the number of neutrons, making heavy-nuclei targets such as active lead-based detectors ideal. In this Letter, we discuss for the first time the physics potential and feasibility of building neutrino detectors using semiconductor lead perovskites crystals as a target. Lead perovskites have emerged in the last decade as revolutionary materials for radiation detection due to their heavy and flexible element composition and their unique optoelectronic properties that result in an excellent energy resolution at an economic cost. In this Letter we indicate that existing data with x-rays suggests the suitability of existing lead perovskites sensor to study CEνNS using neutrinos from π decay at rest (π-DAR) sources. While dedicated research and development will be necessary, we find great benefits and no inherent obstacles for the development of lead perovskites as CEνNS detectors.